The estimation of genetic distance and discriminant variables on breed of duck (Alabio, Bali, Khaki Campbell, Mojosari and Pegagan) by morphological analysis - B Brahmantiyo; L.H Prasetyo; A.R Setioko; R.H Mulyono (Jurnal Ilmu Ternak dan Veteriner, 2003)
A study on morphological body conformation of Alabio, Bali, Khaki Campbell, Mojosari and Pegagan ducks was carried out to determine the genetic distance and discriminant variables. This research was held in Research Institute for Animal Production, Ciawi, Bogor using 65 Alabio ducks, 40 Bali ducks, 36 Khaki Campbell ducks, 60 Mojosari ducks and 30 Pegagan ducks. Seven different body parts were measured, they were the length of femur, tibia, tarsometatarsus, the circumference of tarsometatarsus, the length of third digits, wing and maxilla. General Linear Models and simple discriminant analysis were used in this observation (SAS package program). Male and female Pegagan ducks had morphological size bigger than Alabio, Bali, Khaki Campbell and Mojosari ducks. Khaki Campbell ducks were mixed with Bali ducks (47.22%) and Pegagan ducks from isolated location in South Sumatera were lightly mixed with Alabio and Bali. Mahalanobis genetic distance showed that Bali and Khaki Campbell ducks, also, Alabio and Mojosari ducks had similarity, with genetic distance of 1.420 and 1.548, respectively. Results from canonical analysis showed that the most discriminant variables were obtained from the length of femur, tibia and third digits.   Key words: Duck, genetic distance, morphological